Aligned human induced pluripotent stem cell-derived cardiac tissue improves contractile properties through promoting unidirectional and synchronous cardiomyocyte contraction. (February 2022) - Takada, Takuma; Sasaki, Daisuke; Matsuura, Katsuhisa; Miura, Koichiro; Sakamoto, Satoru; Goto, Hiroshi; Ohya, Takashi; Iida, Tatsuro; Homma, Jun; Shimizu, Tatsuya; Hagiwara, Nobuhisa
Abstract: Alignment, as seen in the native myocardium, is crucial for the fabrication of functional cardiac tissue. However, it remains unclear whether the control of cardiomyocyte alignment influences cardiac function and the underlying mechanisms. We fabricated aligned human cardiac tissue using a micro-processed fibrin gel with inverted V-shaped ridges (MFG) and elucidated the effect of alignment control on contractile properties. When human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were seeded on MFG, hiPSC-CMs were aligned more uniformly than the control, and we succeeded in fabricating the aligned cardiac tissue. Assessing the contractile properties with the direct contractile measurement system, the contractile force, maximum contractile velocity, and relaxation velocity were significantly increased in aligned cardiac tissue compared with non-aligned cardiac tissue. However, gene expression profiles were not different between the two groups, suggesting that functional improvement of cardiac tissue through alignment control might not be dependent on cardiomyocyte maturation. Motion capture analysis revealed that the cardiomyocytes in the aligned cardiac tissues showed more unidirectional and synchronous contraction than the non-aligned cardiac tissues, indicating that cardiac tissue maturation involves electrical integration of cardiomyocytes. Herein, cardiomyocyte alignment control might improve the contractile properties of cardiac tissue through promoting unidirectional and synchronous cardiomyocyte contraction.